In situ encapsulation of Pd inside the MCM-41 channel. Issue 35 (1st April 2015) - Lin, Xi-Jie; Zhong, Ai-Zhi; Sun, Yong-Bin; Zhang, Xing; Song, Wei-Guo; Lu, Rong-Wen; Cao, An-Min; Wan, Li-Jun
Abstract : Pd nanoparticles were successfully introduced into the channels of mesoporous silica MCM-41 with their dispersion well-tuned. Abstract : Pd nanoparticles were successfully introduced into the channels of mesoporous silica MCM-41 with their dispersion well-tuned. We identified the dual role played by CTAB, which was critical for both the micelle template and Pd grafting, leading to the formation of a highly active Pd–MCM-41 nanocomposite for catalysing the Suzuki reaction.